PENGEMBANGAN POTENSI DESA PILANG KECAMATAN MASARAN KABUPATEN SRAGEN MENUJU KAWASAN DESA WISATA - Solichul Hadi; Muladi Wibowo (Asian Journal of Innovation and Entrepreneurship, 2014)
Pilang village is a village in the district Masaran with batik and tourist potential which has not been excavated yet optimally by the government Sragen.This research is a case study with a qualitative descriptive research method, this research aims are: 1). To describe the picture potential of the District Pilang village Masaran Sragendalam District batik field, 2). To describe the picture potential of the District Pilang village Masaran Sragen in the field of Arts and Culture and 3). To formulate development strategies of local culture and art of batik village subdistrict Pilang Masaran Sragen towards Tourism Village.Conclusions of the study: 1). Pilang Rural Development as a tourist village of batik has been backed by local field potential major cultural arts group gong music, 2). Batik Pilang tourist village has great potential but has not been well managed and sustainable. 3). There is a potential gap in the rural area development batik Pilang with Kliwonan village. Suggestions for further study needs to be done by governments and stakeholders on issues of strategic areas of production, marketing, raw materials, involving regional and national stakeholders in order to improve the outlook of batik entrepreneurs, more specifically by conducting a strategic review which resulted in concepts and policies, in particular to increase tourist batik market and village Pilang nationally and internationally    Keywords: Tourism Village, Batik, Cultural Arts